Família na perspectiva do adolescente autor de ato infracional: uma abordagem bioecológica do desenvolvimento humano. - Barros, Beatriz Ribeiro Silveira (2024)
In Brazil, there are records of adolescents, of both genders, involved in and/or perpetrators of an infraction, in compliance with socio-educational warning measures, obligation to repair the damage, provision of service to the community, semi-freedom, assisted freedom and imprisoned, and also in provisional imprisoned or initial care. With this in mind, the importance of the family from the adolescent's perspective was considered so that, in this way, it was possible to discuss their role in the socio-educational process. This research seeks to understand the family relationships of adolescents who commit criminal acts, covering personal, procedural, contextual and temporal aspects between systems from the perspective of the Bioecological Theory of Human Development. Thus, as a problem question, we have: How are adolescents who are perpetrators of and/or those involved in infractions perceiving the role of the family before and during imprisionment? Thus, the general objective of this study was to investigate the role of the family microsystem from the perspective of adolescents who commit and/or are involved in criminal acts. The research included 13 participants, aged 14 to 18, male, in temporary hospitalization, in Pernambuco. The sociodemographic questionnaire and semi-structured interview were used as instruments. To analyze the results, the Thematic Content Analysis technique was adopted, according to Minayo. The main results obtained showed: Adolescents feel love for their family and value the coexistence, advice and income provided; some live for their family and would kill and die for it; have plans to start their own family; and they appreciate visits and phone calls from family members. Some of them pointed out that those responsible were not aware of the infractions; all parents and grandparents do not want them involved in the world of crime; the maternal figure was highlighted; and everyone spoke highly of their families, although some addressed existing conflicts. There were also reports of the intention to protect brothers, as there are cases of brothers who died due to involvement in drug trafficking; and concern for his partner and son was also described.